Supporting decent work and the transition towards formalization through technology-enhanced labour inspection - Michael Gallo; Hannah Thinyane (International Labour Organization (ILO), 2021)
The development and expansion of information and communication technologies (ICTs) has had far-reaching consequences for governance and the world of work, including how labour administrations and inspectorates manage and deliver services. Labour inspection is an essential part of labour administration and ensures the enforcement of worker's rights and compliance with relevant legal obligations. As such, labour inspection is one of the many different pathways available for reducing informality through inspectorates' mandated information sharing and sanctioning activities. An increasing number of governments around the world are interested in exploring, promoting and unlocking the full potential of new technologies to facilitate the transition from the informal to the formal economy. Research and evidence on effective strategies, programs, and practical applications of ICTs in this area to date is limited and policymakers stand to benefit from a greater understanding of what works in addressing informality through technology. In this working paper, we broadly explore the relationship and intersection between labour inspection, technology, and formalization and provide a detailed case study of Apprise, an innovative mobile solution that was developed to assist inspectors and other frontline responders in their preliminary screening of workers for indicators of labour violations and exploitation. Although additional impact evaluation studies are necessary, the study concludes that technology-enhanced labour inspection shows promise as a central component of integrated strategies targeting reductions in informality.
Keywords: 330; decent work; migrant workers; informal economy; labour inspection; COVID-19; information and communication technologies